Model Pemanasan Pencak Silat berbasis Permainan pada Siswa SMA - Rohman, Deden; Rihatno , Taufik; Mustara (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2024)
The aim of this research is to create a game-based pencak silat warm-up model for high school students. The method used is the Research & Development (R&D) method to validate the product in the form of a game-based pencak silat warm-up model for high school students. In this research there are 5 stages, namely: Analysis, Design, Development, Implementation and Evaluation. In this research study, it was verified by 1 learning expert, 1 pencak silat expert and 1 physical education teacher. The validation test used is an expert justification test, where the heating model that has been created and developed is tested first, then consulted and assessed by experts. Verification by experts resulted in a game-based pencak silat warm-up model for high school students. The game-based pencak silat warm- up model for high school students was developed to be more varied and innovative.